Student Perceptions of Effective E-moderation: A Qualitative Investigation of E-College Wales - Thomas, Brychan; Jones, Paul; Packham, Gary; Miller, Christopher (Proceedings of the International Conference on Networked Learning, 2004)
This study examines student perceptions of effective e-moderation and contrasts against existing literature. The study investigates the online BA Enterprise offered by the University of Glamorgan, supported by “Blackboard” software. The methodology involved interviews with 35 students using a semi-structured questionnaire to elicit responses on perceptions of effective e-moderation. Questionnaire analysis revealed that students identified quality and quick turnaround of feedback, availability of a tutor at key times and approachability as constituents of effective e-moderation. The e-moderator was characterised as a councillor, tutor and subject specialist. This study can be utilised by e-learning practitioners to develop an effective code of practice for e-moderators.